Altered Mitochondria, Protein Synthesis Machinery, and Purine Metabolism Are Molecular Contributors to the Pathogenesis of Creutzfeldt–Jakob Disease. Issue 8 (August 2016) - Ansoleaga, Belén; Garcia-Esparcia, Paula; Llorens, Franc; Hernández-Ortega, Karina; Carmona, Margarita; Antonio del Rio, José; Zerr, Inga; Ferrer, Isidro
Abstract : Neuron loss, synaptic decline, and spongiform change are the hallmarks of sporadic Creutzfeldt–Jakob disease (sCJD), and may be related to deficiencies in mitochondria, energy metabolism, and protein synthesis. To investigate these relationships, we determined the expression levels of genes encoding subunits of the 5 protein complexes of the electron transport chain, proteins involved in energy metabolism, nucleolar and ribosomal proteins, and enzymes of purine metabolism in frontal cortex samples from 15 cases of sCJD MM1 and age-matched controls. We also assessed the protein expression levels of subunits of the respiratory chain, initiation and elongation translation factors of protein synthesis, and localization of selected mitochondrial components. We identified marked, generalized alterations of mRNA and protein expression of most subunits of all 5 mitochondrial respiratory chain complexes in sCJD cases. Expression of molecules involved in protein synthesis and purine metabolism were also altered in sCJD. These findings point to altered mRNA and protein expression of components of mitochondria, protein synthesis machinery, and purine metabolism as components of the pathogenesis of CJD.